Bridging the Digital Divide: A Mixed-Methods Evaluation of the Efficacy, Accessibility, and Impact of Web-Based Mental Health First Aid Training for Community Health Volunteers (Kader) in Rural Indonesia - Zahra Amir; Ni Made Nova Indriyani; Iis Sugandhi; Husin Sastranagara; Muhammad Rusli; Wisnu Wardhana Putra (HM Publisher, 2025)
Significant disparities in mental health service access persist in rural Indonesia, where community health volunteers (known as Kader) represent a vital but undertrained resource. Digital training platforms offer a scalable solution to build mental health literacy, yet their efficacy and accessibility in low-resource, digitally diverse settings remain under-evaluated. This study aimed to evaluate the efficacy, accessibility, and user experience of a novel, web-based Mental Health First Aid (MHFA) training program for Kader in rural Indonesia. We employed a convergent parallel mixed-methods design with a single-group, pre-test/post-test framework. A total of 165 Kader from 15 rural districts across North Sumatra, West Sumatra, and South Sumatra provinces were recruited. Participants completed a 4-week, self-paced, web-based MHFA course. Quantitative data were collected using the Mental Health Knowledge Questionnaire (MHKQ), the Community Attitudes toward the Mentally Ill (CAMI) scale, and the System Usability Scale (SUS) at baseline and post-intervention. Qualitative data were gathered through semi-structured focus group discussions (FGDs) with a purposive subsample of 32 participants to explore user experience and perceived impact. The intervention yielded a highly significant improvement in mental health knowledge, with mean MHKQ scores increasing from 48.5 (SD=10.2) at pre-test to 89.7 (SD=8.8) at post-test (t(164) = -35.1, p < 0.001). Stigmatizing attitudes significantly decreased, as reflected by an increase in mean CAMI scores from 55.3 (SD=12.5) to 81.4 (SD=11.9) (t(164) = -18.9, p < 0.001). The platform's usability was rated favorably, with a mean SUS score of 81.2 (SD=13.4), indicating excellent user-friendliness. Qualitative analysis revealed three primary themes: (1) Digital Empowerment and Overcoming Barriers; (2) Cultural Resonance and Practical Skill Acquisition; and (3) The Emergence of a Supported Community of Practice. In conclusion, web-based MHFA training is an effective, accessible, and well-accepted modality for empowering Kader in rural Indonesia. This digital approach successfully bridges geographical and educational divides, significantly enhancing mental health literacy and reducing stigma. Scaling this model holds immense potential for strengthening community-based mental health services and narrowing the treatment gap in Indonesia and similar low- and middle-income countries.